Category A + C passage in the light of applicable regulations - Paweł Ukleja (Przegląd Komunikacyjny)
Abstract: Modern crossing systems made in computer technology, thanks to their modular structure and configuration flexibility, fully meet the requirements set for them. Their implementation is possible on all categories of railroad crossings with safety devices in typical and non-standard configurations. Computer technology makes their operation easy and ensures the highest security standards Keywords: A category crossing; BUES 2000